Pcgra: uma arquitetura de referência para geração procedural de conteúdo em jogos digitais - So, Arthur Riuiti Pinheiro (2025)
architectures that provide generation capabilities in games. This study aims to improve the adoption of PCG by providing a reference architecture that meets the requirements outlined in the literature, as well as presenting an analysis of existing architectures. To achieve this, a systematic mapping was conducted, reviewing 121 publications; from these, nine studies were selected through database searches, snowballing, and manual search. Using these studies as a source to extract software requirements, a process called ProSA-RA was employed to design a reference architecture, named PCGRA, which was evaluated through interviews with software engineering professionals. As an additional form of architecture validation, a game was developed and used to measure the characteristics of the requirements. The selected studies indicate trends toward modular, scalable, and user-centered architectures, with a primary focus on content adaptation to the user, orchestration of different content aspects, and accessibility for designers to make use of PCG. Based on this, the proposed architecture, PCGRA, demonstrated good performance in metrics related to modularity, extensibility, maintainability, and performance.